The Drill and Practice Method for Teaching the Simple Past Tense to Non-English Major Students - Zuvyati Aryani Tlonaen (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2025)
This study aims to improve the understanding of the simple past tense among non-English major students using the drill and practice method. The study employed a one-group pre-test-post-test design. The sample consisted of 62 first-semester theology students enrolled in the General English course at Universitas Kristen Artha Wacana, Indonesia. The pre-test was conducted by testing ten items on the simple past tense, covering affirmative, negative, and interrogative forms. Subsequently, students participated in DP sessions, which included material introduction, modeling, guided practice, immediate feedback, repetition practice, individual assessment, discussion and clarification, independent practice, reinforcement, and closing. Following the intervention, a post-test was conducted to measure improvements in understanding. The data were analyzed using the Wilcoxon test. Results indicated a significant improvement in students’ understanding of simple past tense, with a Wilcoxon value of -4.936 and asymptotic significance below 0.001. Additionally, accuracy rates and response times improved, while the number of unanswered questions decreased. The study concludes that the DP method, combined with targeted feedback, is effective in enhancing grammar skills for non-English major students, although some learners may require further instructional adjustments. While the study reports positive outcomes, it lacks a discussion of limitations, including its single group design, limited generalizability due to the specific institution, and the absence of a control group. Future research should address these limitations by investigating long-term effects and involving larger sample sizes.